2010
DOI: 10.4103/0256-4947.71061
|View full text |Cite
|
Sign up to set email alerts
|

K469E polymorphism of the intercellular adhesion molecule-1 gene in Egyptians with coronary heart disease

Abstract: BACKGROUND AND OBJECTIVES:The initial step in atherosclerosis is the adhesion of leukocytes to activated endothelial cells mediated by intercellular adhesion molecule-1 (ICAM-1). This study aimed to investigate the association of K469E polymorphism of the ICAM-1 gene and soluble ICAM-1 (sICAM-1) serum level with coronary heart disease (CHD) in Egyptian subjects.PATIENTS AND METHODS:Using a case-control design, we studied 100 patients with CHD, including 73 patients with acute myocardial infarction (MI) and 27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
(15 reference statements)
1
8
0
Order By: Relevance
“…Lu et al (17) used nested PCR with allele-specific oligonucleotide primers in 160 patients with CHD and 64 control subjects and found that the A allele frequency and plasma levels of ICAM-1 were higher in patients with CHD than those in control subjects. It was also found that the frequency of the A genotype (AG and GG) was significantly higher in patients with CHD than that in controls in the Egyptian population (18). However, McGlinchey et al (19) found that rs5498 was not associated with ischemic heart disease in Irish populations.…”
Section: Discussionmentioning
confidence: 96%
“…Lu et al (17) used nested PCR with allele-specific oligonucleotide primers in 160 patients with CHD and 64 control subjects and found that the A allele frequency and plasma levels of ICAM-1 were higher in patients with CHD than those in control subjects. It was also found that the frequency of the A genotype (AG and GG) was significantly higher in patients with CHD than that in controls in the Egyptian population (18). However, McGlinchey et al (19) found that rs5498 was not associated with ischemic heart disease in Irish populations.…”
Section: Discussionmentioning
confidence: 96%
“…The frequencies of KK and EK genotypes in patients with MI showed no significant difference compared to patients with unstable angina [18].…”
Section: Discussionmentioning
confidence: 96%
“…The single nucleotide C to T polymorphism in the sixth exon of the ICAM-1 gene (K469E) results in an amino acid substitution from glutamic acid (E) to lysine (K) in immunoglobulin-like domain 5 of the ICAM-1 protein. This polymorphism has been reported to be involved in inflammatory diseases and atherosclerosis [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…There are several points that worth noting about this meta‐analysis. First, the rs5498 polymorphism causes an amino acid change from glutamic acid (E) to lysine (K), which is proved to be associated with alteration in protein structure and binding affinity of ICAM‐1 protein (He et al, ; Mohamed et al, ). Thus, it is possible that rs5498 polymorphism may impact biological function of ICAM‐1, give rise to the development of over‐activated inflammatory reactions, and ultimately influence individual susceptibility to IS.…”
Section: Discussionmentioning
confidence: 99%